أسباب انتشار الدروس الخصوصية في المرحلة الثانوية من وجهة نظر التلاميذ (دراسة ميدانية على عينة من ثانويات مدينة سعيدة) - مصطفاوي, بوعناني; كورات, كريمة (جامعة الوادي - University of Eloued, 2018)
هدف البحث للتعرف على الأسباب المؤدية لانتشار الدروس الخصوصية لدى تلاميذ المرحلة الثانوية بمدينة سعيدة من وجهة نظرهم في ضوء متغير الجنس و التخصص،لهذا الغرض تم إعداد استبيان مكون من (25) بندًا لقياس أسباب انتشار الدروس الخصوصية لدى تلاميذ المرحلة الثانوية ، تكونت عينة البحث من (200) تلميذ و تلميذة من أقسام السنة الثالثة ثانوي المقبلين على امتحان البكالوريا،تم اختيارهم بطريقة عشوائية،وبعد المعالجة الإحصائية أسفر البحث على النتائج الآتية: - تنتشر الدروس الخصوصية بشكل كبير بين تلاميذ المرحلة الثانوية في مختلف التخصصات (العلمية و الأدبية) -وجود فروق دالة إحصائيا بين متوسط استجابات الجنسين لأسباب انتشار الدروس الخصوصية تبعًا لمتغير الجنس لصالح الإناث. -توجد فروق ذات دلالة إحصائية في درجة الاقتناع بأسباب أخذ الدروس الخصوصية تبعًا لمتغير التخصص لصالح التلاميذ ذوي التخصص العلمي.The research aims to identify the causes of the proliferation of private lessons to secondary students in the variables of sex and specialty, The Search Tool is uestionnaire to identify the causes of the proliferation of private lessons to the pupils in secondary education, The sample was (200) students and pupils were selected randomly, resulting in research on the following results: -spread lessons Privacy Policy significantly among secondary students in various disciplines (scientific and literary) There are a statistically significant differences between males and females to the cause for the spread of private lessons, depending on the variant of sex for the benefit of the female. -There were no statistically significant differences in the degree of the reasons for taking the lessons privacy depending on the variable speciality in favor of students with scientific specialization
The causes of the spread of private lessons from the point of view of the secondary education
مقال
Keywords: الدروس الخصوصية، مرحلة التعليم الثانوي; Lessons Privacy , secondary education